Performance-related pay and employees responses in the Chinese education system - Huang, B.; Shen, Jie (Kluwer Law International, 2011)
Human resource management in the Chinese public sector has been largely under-researched. This study explores performance-related pay (PRP) practices and employees' responses to these practices in the Chinese education system. It concludes that the PRP scheme has been widely implemented in China and has been well received by Chinese high school teachers in terms of improving employee performance. Chinese high school teachers highly regard PRP for three reasons: first, PRP, as 'prize money', is believed to increase employee income; second, itemized performance criteria help reduce subjectivity; and third, small differences in PRP between employees mitigate unhealthy competition. This study adds to the knowledge base of PRP in the public sector.